2003
DOI: 10.1562/0031-8655(2003)078<0342:msureo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Measured Solar Ultraviolet Radiation Exposures of Outdoor Workers in Queensland in the Building and Construction Industry¶

Abstract: The risk to outdoor workers of exposure to solar ultraviolet radiation (UVR) has been known for some time, particularly in the building and construction industry, where workers often use little in the way of protection against solar UVR. In recent years there have been attempts by authorities in Australia and in Queensland in particular, where UVR levels in spring and summer are very high to extreme, to instigate and to encourage the use of personal UVR protection by outdoor workers. To quantify UVR exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
153
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(171 citation statements)
references
References 28 publications
17
153
0
1
Order By: Relevance
“…For building workers, the mean daily concurrent ER was 19.6 % on the back, with a range of 1.6 to 66.4, whereas we obtained a median ER of 14.5% (range 2.3-55.0) on the shoulder (comparable to the back area). Gies and Wright, 2003 examined UVR exposure in some groups of outdoor workers related to the construction industry in Australia in the spring. They found that a formworker received a median concurrent ER of 30% and a steel fixer of 33%, both on the chest, whereas we measured a median ER of 9% and 42%, respectively, on the chest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For building workers, the mean daily concurrent ER was 19.6 % on the back, with a range of 1.6 to 66.4, whereas we obtained a median ER of 14.5% (range 2.3-55.0) on the shoulder (comparable to the back area). Gies and Wright, 2003 examined UVR exposure in some groups of outdoor workers related to the construction industry in Australia in the spring. They found that a formworker received a median concurrent ER of 30% and a steel fixer of 33%, both on the chest, whereas we measured a median ER of 9% and 42%, respectively, on the chest.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its geographical situation, for most of the year the Valencia Region (Spain) receives large doses of UVR. Outdoor workers receive regular and significant solar UVR in their course of their activities (Gies and Wright, 2003;Gies et al, 2009;Glanz et al, 2007;Hammond et al, 2009;Milon et al, 2007;Moehrle et al, 2003;Schmalwieser et al, 2010;Serrano et al, 2009;Siani et al, 2011;Siani et al, 2008;Thieden et al 2005) especially when solar radiation is intense.…”
Section: Introductionmentioning
confidence: 99%
“…UV exposure is specific to the formation of the above health effects and much research has been conducted to measure and model UV exposure. UV radiation is influenced by (and UV exposure modelling must take into account) many atmospheric factors; including solar zenith angle, altitude, latitude, ozone, clouds, aerosols, albedo (reflectivity) [3,4] and personal factors; including occupation and personal behaviour [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…10 It has previously been shown that outdoor workers can be exposed to excessive levels of UV exposure, and that UV exposure is dependent on the occupation. 8,11 Studies also show that most outdoor workers often exceed occupational recommended UV exposure levels. [11][12][13] Recommendations for occupational UV exposure levels are readily available.…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Studies also show that most outdoor workers often exceed occupational recommended UV exposure levels. [11][12][13] Recommendations for occupational UV exposure levels are readily available. 14,15 UV exposure to outdoor workers can be managed; however factors that affect UV exposure need to be assessed in order to determine appropriate recommendations to outdoor workers.…”
Section: Introductionmentioning
confidence: 99%